Women’s Reistance Against Hegemony In Nathaniel Hawthorne’s The Scarlet Letter and Ahmad Tohari’s Bekisar Merah: A Comparative Study - Pritania V. V. Mokalu; Tini Mogea; Elisabeth Z. Oroh (Journal of English Language Teaching, Literature and Culture, 2023)
Hegemony is a dominance treatment from one to another. This article tried to compare women’s resistance against hegemony from novels. Lasiyah, the protagonist in Bekisar Merah, and Hester Prynne, the protagonist in The Scarlet Letter, both encountered oppressive hegemonic values from their patriarchal societies, namely Javanese and Puritans. Using Hegemony and Comparative Literature theories, this research reveals the two protagonists' resistance to hegemonic values, which caused them to become new people with new personalities and identities. They were also reborn. Both women were motivated by similar factors, such as pride and dignity, to engage resistance. Women, who are generally regarded as weak and powerless, are, in fact, strong and powerful.